CT texture analysis in colorectal liver metastases and the surrounding liver parenchyma and its potential as an imaging biomarker of disease aggressiveness, response and survival. Issue 102 (May 2018) - Beckers, R.C.J.; Trebeschi, S.; Maas, M.; Schnerr, R.S.; Sijmons, J.M.L.; Beets, G.L.; Houwers, J.B.; Beets-Tan, R.G.H.; Lambregts, D.M.J.
Highlights: Assessing ratios between texture of liver metastases and surrounding-liver can be valuable. Ratios between texture features are capable of assessing extent of disease. Emetastases /Eliver ratio is associated with survival, albeit not significant. Abstract: Objectives: To study the ratio between the CT texture of colorectal liver metastases (CRLM) and the surrounding liver parenchyma and assess the potential of various texture measures and ratios as predictive/prognostic imaging markers. Materials: Seventy patients with colorectal cancer and synchronous CRLM were included. All visible metastases, as well as the whole-volume of the surrounding liver, were separately delineated on the portal venous phase primary staging CT. Texture features entropy (E) and uniformity (U) were extracted and ratios between the texture features (T) of the metastases and background liver (Tmetastases /Tliver ) calculated. Texture features were compared with clinical outcome parameters: [1] extent of disease (i.e. number of metastases), [2] response to chemotherapy (in 56/70 patients who underwent chemotherapy and CT for response evaluation), and [3] overall survival. Results: The Emetastases /Eliver ratio was lower in patients with limited disease ( P = 0.02) and associated with overall survival, albeit not statistically significant when tested in multivariable analyses (HR 1.90; P = 0.07); Umetastases /Uliver was higher in patients with limited disease ( P = 0.02). Emetastases showed a trend towards a higher value in patients that responded well to chemotherapy ( P = 0.08). Conclusion: The ratio between the texture of liver metastases and the surrounding liver appears to reflect relevant changes in tissue microarchitecture and may be of value to assess the extent of disease and help predict overall survival.